Dynamic ROS Production and Gene Expression of Heifers Blood Neutrophil in a Oligofructose Overload Model - Li, Shuaichen; Ding, Jiafeng; Jiang, Lihong; Hayat, Muhammad Abid; Song, Qiaozhi; Li, Yuepeng; Zhang, Xianhao; Zhang, Jiantao (Frontiers in Veterinary Science, 2020)
Alimentary oligofructose (OF) overload can induce several diseases in cattle, such as ruminal acidosis, laminitis, and synovitis. The role of blood polymorphonuclear neutrophil (PMN) remains unclear during OF overload. The aim of this study was to investigate the dynamic changes in reactive oxygen species (ROS) production and the expression profile of genes in blood PMN in a model of OF overload. Twelve clinically healthy and non-pregnant Chinese Holstein heifers, aged between 18-26 mo, weighing 335-403 kg, BCS (5-point scale) ranges 2.7-3.3 were used for the experiments. OF heifers (n = 6) received 17 g/kg of BW oligofructose dissolved in 2 L/100kg of BW tap water and the CON heifers (n = 6) received 2L/100kg of BW tap water. Blood PMN was isolated for each heifer 0, 6, 12, 18, 24, 36, 48, 60, and 72 h after administration. PMN was analyzed either by endogenous and phorbol myristate acetate (PMA)-induced ROS production or by quantitative real-time PCR. After 12 h, PMA-induced ROS production decreased, which was sustained until 48 h. The expressions of inflammation markers (IL1α, IL1β, IL6, IL10, TNFα, STAT3, TLR4, MMP9, and HP) and eicosanoids (ALOX5, ALOX5AP, and PLA2G4A) were upregulated. The expression of adhesion and migration (CXCR2, CXCL8, CD62L, ITGA4, ITGAM, and ITGB2) in OF heifers was increased compared with CON heifers. The expression of oxidative stress (SOD2 and S100A8) was upregulated, while SOD1 and MPO were downregulated. In metabolism and receptor genes, the expressions of GRα and INSR decreased after 18 h, while Fas increased until 6 h and then decreased at 18 h. The expression of LDHA and PANX1 did not show any differences after OF overload. These findings indicate that OF overload induced systemic activation of PMN, which provides a step toward a better understanding of the role of innate immune responses in response to oral OF administration.